A model for analyzing compensation for the treatment costs of construction waste. (August 2021) - Liu, Jingkuang; Yi, Yanqing; Li, Clyde Zhengdao; Zhao, Yiyu; Xiao, Yanqing
Abstract: Global governments only collect landfill taxes and fees for the disposal of most construction waste and ignore discount and economic compensation measures. Thus, stimulating construction contractors' enthusiasm for recycling waste resources becomes difficult, and construction waste utilization remains at a comparatively low level. This study first constructs a compensation model of evolutionary game for construction waste treatment costs, wherein the government, developer, and contractor are the players. It aims to solve the corresponding game equilibrium points. Then, this work establishes a stock-flow diagram of the evolutionary game among the three players using the system dynamics principle to analyze the stability of the local equilibrium points obtained during the evolutionary game. The research conclusion can improve the theory of construction waste management in the theoretical contribution, especially in the field of economic incentive theory. On the other hand, the practical significance of this paper lies in exploring the active measures to lead the contractors and developers willing to recycle and reuse waste, and promoting the recycling rate of construction waste.